Naked-Eye Detection of Lead Ion in Water sample using Reagent Extracted from White Dragon Fruit Peel - เขาดี, วรางคณา; วงศ์กิติ, รติกร; มาแดง, สุพัตรา (KKU Science Journal, 2017)
This study focused on the qualitative and quantitative necked-eye detection of metal ion in water sample using reagent extracted from plants. Betacyanin could be extracted from white dragon fruit peel using ethanol as a solvent, and the interaction between betacyanin and metal ion was then examinated along with the effect of pH. Pb2+ was found to be able to clearly change the color of betacyanin under buffer solution pH 6. The optimum condition for the detection of Pb2+ was observed by adding 10 µL of reagent in the mixture of 500 µL of 0.01 M buffer pH 6 and 200 µL of water sample. The detection limit of naked-eye detection was 3x10-4 M without interference from other ions, except sulphate ion. This developed method also showed correlated results comparing with AAS technique.